COLLECTION OF AUTOGRAPHS IN MODERN LITHUANIA - GUSTAITIS, ROLANDAS (Knygotyra, 2015)
Collection of autographs emerged in Europe in the sixteenth century, together with the spread of the written language. In later centuries, this type of collection became popular in many European countries and USA. Relevant media articles and rare exhibitions of autographs show that although collection of autographs does exist in Lithuania as a particular type, knowledge about it is limited. Both autographs and, in general, their collection are the subject of limited scientific research in Lithuania. However, collection of autographs as a phenomenon is out of the scope of the aforementioned research. The present article examines the current Lithuanian collectors of autographs, their collecting motives, thematic composition of collections, methods of collection and sources of collections. The research revealed that collection of autographs is an integral part of certain Professional activity and leisure time of collectors, which is related and complementary to it. Among Lithuanian collectors of autographs, the most popular are the autographs of contemporary famous Lithuanian representatives of art, culture, science, public, politics and sports as well as famous foreign musicians and actors. Personalities, but not themes are selected, the autographs of famous persons, but not of all famous persons of a certain historical period are collected. The autographs of Lithuanian historic personalities, subject to a negative attitude, are not popular as the objects of collection. In Lithuania, the most popular are eclectic (mixed) collections, which consist of unrelated autographs on various themes that are close to the collector. The most important criterion for selection of autographs for these collections is an emotional and intellectual attractiveness of an autograph. It might be argued that even the autographs of negatively viewed personalities can be valuable, if certain historical periods rather than individual persons are chosen as the objects of collection. Thus, selection of themes rather than persons would allow to fully reveal complex epochs of Lithuanian history (wars, occupations), while the aforementioned thematic collections of autographs could be successfully used as iconographic material, for example, to illustrate historical monographs or other works in publishing, or used as educational tool for lectures, etc. Lithuanian collectors usually acquire the autographs of historical persons by purchasing them (in flea markets, antique shops, from other collectors, etc.), while the collectors of autographs of contemporary people generally ask for them personally during various events (concerts, book presentations, etc.). It might be concluded that subject to the nature of collection (of historical persons or collector’s contemporaries), the methods of autograph collection and their sources differ. Personally obtained autographs are the most popular and the most common method to collect autographs in Lithuania. In this way, the collectors get autographs from the following sources: 1) during various events (during concerts, book presentations, scientific conferences); it is the most popular source of autographs; 2) in workplaces, 3) by post after sending the request for autograph to the preferred author; even though this source of obtaining autographs is the most rare. Other methods to collect autographs are the following: 1) through intermediary (the sources are similar as getting the autograph personally); 2) purchase (flea market, antiques, auctions, etc.), 3) gift, 4) accidental findings. In comparison with methods of collecting books (purchase, exchange, gifts, heritage), no exchange of autographs and no heritage cases are found among the current Lithuanian collectors of autographs.
Keywords: ...